Asinine milk: animal health and welfare - Farias, Sharacely de Souza (2022)
In Brazil, donkeys have lost their economic value and since 2016, have not been accounted for by the Brazilian Institute of Geography and Statistics (IBGE). As a consequence, their abandonment has been intensified. Most of these animals are found in the northeastern region of Brazil (80%) and their expressive numbers have caught the attention of Chinese markets, which have attempted to establish the slaughter and commercialisation of donkey skin as a means to reintroduce them into the brazilian economy. Therefore, this study aims to contextualise the social, economical and cultural situation of donkeys in Brazil, assess the welfare conditions of donkeys destined for slaughter, and explore possibilities of reintroducing donkeys in the brazilian economy through the sustainable and ethical production of asinine milk. A case study was conducted to assess the welfare of abandoned donkeys (Farias, 2021a), an experiment to assess the welfare of jennies during milking (Farias, 2021b), other about physical and chemical parameters of asinine milk of the Pêga breed and a study on the effects of supplementation with asinine milk on behaviour, productive parameters and immunity of piglets before and after weaning. The studies concluded that it is observable that asinine milk samples collected in this study did not suffer composition changes throughout lactation, which is in agreement with other studies with donkey and mare milk and supplementation with asinine milk did modulate the expression of genes related to inflammation, resulted in a decrease in salivary cortisol post-weaning in the afternoon, and did not alter the behavioural expression of stress in the tests conducted. Therefore, further studies on the supplementation with asinine milk are warranted. All data were analysed in the SAS software and for all presented tests, average pairs were compared to 5% probability. The objective of this study is to explore possibilities of reintroduction of donkeys in the brazilian social and economic scenarios through the sustainable and ethical production and commercialisation of asinine milk.